Transformasi Manajemen Pembinaan Kesiswaan Berbasis Boarding School Menuju Madrasah Efektif Dan Berprestasi - Riyuzen Praja Tuala; Muh. Nur Islam Nurdin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This research aims to analyze and describe boarding school-based student development management towards effective and high-achieving madrasas at Madrasah Aliyah Negeri 1 Bandar Lampung City. The research method used is descriptive qualitative. Data collection techniques through in-depth interviews, non-participant observation, and documentation. The data analysis technique uses the Miles, Huberman and Saldana interactive model with data condensation activities, data presentation and drawing conclusions. Test the validity of the data using source triangulation and technical triangulation. The research results show that managerial steps, starting with planning, organizing, mobilizing and supervising, are in line with the principles of school-based management which supports the creation of a conducive and effective environment for developing students' potential. This managerial transformation has proven to have a positive impact on madrasas, such as increasing academic and non-academic achievements, forming students' characters who are more disciplined, religious and independent as well as improving the public's image and trust in madrasas. Various strategies to overcome obstacles, such as increasing budgets, better coordination, and improving the quality of dormitory supervisors, need to be implemented comprehensively and continuously. This research contributes to understanding the importance of the transformational steps in boarding school-based student development management as an effort to create effective and high-achieving madrasas. Penelitian ini bertujuan menganalisis dan mendeskripsikan manajemen pembinaan kesiswaan berbasis boarding school menuju madrasah yang efektif dan berprestasi di Madrasah Aliyah Negeri 1 Kota Bandar Lampung. Metode penelitian yang digunakan adalah deskriptif kualitatif. Teknik pengumpulan data melalui wawancara mendalam, observasi non partisipan, dan dokumentasi. Teknik analisis data menggunakan model interaktif Miles, Huberman dan Saldana dengan kegiatan kondensasi data, penyajian data, dan penarikan kesimpulan. Uji Keabsahan data menggunakan triangulasi sumber dan triangulasi teknik. Hasil penelitian menunjukkan langkah-langkah manajerial dimulai perencanaan, pengorganisasian, penggerakan, dan pengawasan telah selaras dengan prinsip-prinsip manajemen berbasis sekolah yang mendukung terciptanya lingkungan yang kondusif dan efektif bagi pengembangan potensi peserta didik. Transformasi manajerial tersebut terbukti berdampak positif bagi madrasah seperti peningkatan prestasi akademik maupun non akademik, membentuk karakter siswa yang lebih disiplin, religius, dan mandiri serta meningkatkan citra dan kepercayaan masyarakat terhadap madrasah. Berbagai strategi mengatasi hambatan, seperti peningkatan anggaran, koordinasi yang lebih baik, dan peningkatan kualitas pembina asrama, perlu diterapkan secara komprehensif dan berkesinambungan. Penelitian ini berkontribusi memberikan pemahaman pentingnya transformasi manajemen pembinaan kesiswaan berbasis boarding school sebagai upaya menciptakan madrasah yang efektif dan berprestasi.